VISUALISASI DATA UPTD PUSKEMAS DALAM BENTUK INFOGRAFIS DI KECAMATAN METRO PUSAT - Utami, Winda Afrilia; Muharni, Sita (LP2M Institut Informatika Dan Bisnis Darmajaya, 2025)
This study aims to improve the effectiveness of health information delivery through data visualization in infographic form at the UPTD Public Health Center (Puskesmas) of Metro Pusat District, Indonesia. Conventional health reports are often too long and complex for stakeholders and the public to interpret, so the underlying data is rarely used to its full potential in planning and decision-making. This research applies the Visual Data Mining (VDM) method, covering project planning, data preparation, and data analysis, with Tableau used as the visualization tool. The dataset consists of new-case and existing-case records for the ten most frequent diseases registered at Puskesmas Metro Pusat from 2021 to 2024, drawn from 45 recorded disease categories. The resulting dashboard shows that Hypertension (ICD-10 I10) is consistently the most frequent diagnosis across all four years, while several respiratory and metabolic conditions show distinct rising or falling trends between 2021 and 2024. These findings indicate that infographic-based visualization can present multi-year health trends in a more interactive, accurate, and easily interpreted format than narrative reports, supporting more responsive, evidence-based decision-making at the primary care level. The study recommends infographic-literacy training for Puskesmas staff, development of digital dissemination tools, and cross-sector collaboration to widen public access to health information.